Incidence and predictors of prosthesis–patient mismatch after TAVI using SAPIEN 3 in Asian: differences between the newer and older balloon-expandable valve. Issue 1 (18th March 2021) - Miyasaka, Masaki; Tada, Norio; Taguri, Masataka; Kato, Shigeaki; Enta, Yusuke; Hata, Masaki; Watanabe, Yusuke; Naganuma, Toru; Yamawaki, Masahiro; Yamanaka, Futoshi; Shirai, Shinichi; Ueno, Hiroshi; et al.
Abstract : Background: The balloon-expandable SAPIEN 3 (S3) is superior to the older-generation balloon-expandable SAPIEN XT (XT) in a lower incidence of paravalvular aortic regurgitation, lower complication rates and better survival in transcatheter aortic valve implantation (TAVI). However, prosthesis–patient mismatch (PPM) more frequently occurs in S3 than XT. Further, little information is available on PPM after TAVI using S3 in Asians. This study aims to determine the incidence and predictors of PPM in S3 by focusing on the difference between S3 and XT using data from a Japanese multicentre registry. Methods: From the Optimised transCathEter vAlvular iNtervention-TAVI (OCEAN-TAVI) registry, 2134 patients undergoing TAVI using S3 or XT were included. PPM was defined as moderate if ≧0.65 but ≦0.85 cm 2 /m 2 or severe if <0.65 cm 2 /m 2 at the indexed effective orifice area by postprocedural echocardiography. Results: The incidence of moderate and severe PPM in S3 was 13.3% and 1.3%, respectively. The 20 mm transcatheter heart valve (THV) was more frequently used in S3 than XT (7.4% vs 2.4%, p<0.0001). PPM was more frequently observed in S3 than XT (14.7% vs 8.8%, p<0.0001). Multivariate logistic regression analysis revealed S3 predicted PPM (OR 1.92 (95% CI 1.35 to 2.74), p=0.0003). The mutual predictors for PPM between S3 and XT were younger age, larger body surface area, smaller aortic valve area, no balloon postdilatation and the use of 20 mm and 23 mm THV. When comparing 23 mm, 26 mm and 29 mm S3, the ORs of 20 mm S3 were 5.67 (95% CI 2.88 to 11.12), 19.24 (95% CI 8.13 to 46.86) and 51.03 (95% CI 12.28 to 280.77), respectively. Conclusions: The incidence of PPM after TAVI using S3 was 14.6% overall in this Asian population. PPM was more frequently observed in S3 than XT. A considerable number of patients were treated by the 20 mm S3 in an Asian cohort. The 20 mm THV was identified as a strong predictor for PPM.